# Difference between revisions of "Delta derivative of quotient"

From timescalewiki

Line 3: | Line 3: | ||

$$\left( \dfrac{f}{g} \right)^{\Delta}(t) = \dfrac{g(t)f^{\Delta}(t)-f(t)g^{\Delta}(t)}{g(t)g(\sigma(t))},$$ | $$\left( \dfrac{f}{g} \right)^{\Delta}(t) = \dfrac{g(t)f^{\Delta}(t)-f(t)g^{\Delta}(t)}{g(t)g(\sigma(t))},$$ | ||

where $\sigma$ denotes the [[forward jump]]. | where $\sigma$ denotes the [[forward jump]]. | ||

+ | |||

+ | ==Proof== | ||

==References== | ==References== | ||

* {{BookReference|Dynamic Equations on Time Scales|2001|Martin Bohner|author2=Allan Peterson|prev=Delta derivative of product (2)|next=Delta derivative of classical polynomial}}: Theorem 1.20 (v) | * {{BookReference|Dynamic Equations on Time Scales|2001|Martin Bohner|author2=Allan Peterson|prev=Delta derivative of product (2)|next=Delta derivative of classical polynomial}}: Theorem 1.20 (v) | ||

+ | |||

+ | [[Category:Theorem]] | ||

+ | [[Category:Unproven]] |

## Latest revision as of 05:44, 10 June 2016

## Theorem

Let $\mathbb{T}$ be a time scale, $t \in \mathbb{T}^{\kappa}$, $f,g \colon \mathbb{T} \rightarrow \mathbb{R}$ delta differentiable, and $g(t)g(\sigma(t)) \neq 0$. Then $\dfrac{f}{g}$ is delta differentiable and $$\left( \dfrac{f}{g} \right)^{\Delta}(t) = \dfrac{g(t)f^{\Delta}(t)-f(t)g^{\Delta}(t)}{g(t)g(\sigma(t))},$$ where $\sigma$ denotes the forward jump.

## Proof

## References

- Martin Bohner and Allan Peterson:
*Dynamic Equations on Time Scales*(2001)... (previous)... (next): Theorem 1.20 (v)